ASPEK PERLINDUNGAN HUKUM TERHADAP KONSUMEN JASA PERUSAHAAN LISTRIK NEGARA (JURNAL HUKUM SEHASEN, 2019)
This study focuses on aspects of legal protection for consumers of state electricity companies and whether consumers of state electricity companies are provided protection. This study uses a socio-legal approach that primarily performs qualitative methods, based on literature data. Using a socio-legal approach, this research will carry out two types of approaches, which are normative social and legal. This study provides consumers with the protection of state electricity companies where settlement of out-of-court disputes is carried out through the Consumer Protection Foundation (YPK) and if it is unsuccessful, then the lawsuit is carried out through the District Court. Keywords: Legal Protection, Consumers.